Práticas de gestão do conhecimento no Programa Esporte e Lazer da Cidade e Vida Saudável - Cristina Carvalho de Melo; Tatiana Lima Boletini; Ana Cláudia Porfirio Couto
RESUMO Collecting, managing and disseminating the information and knowledge produced is an essential part of Knowledge Management. Thus, the objective of this study was to analyze the practices of CG in the Programa Esporte e Lazer da Cidade e Vida Saudável (PELC/VS). Data were collected through questionnaires, answered by 15 PELC/VS trainers and articulators. To analyze the qualitative data, we performed content analysis. The KM practices identified were: "Modular training", "Local community observation", "Record of lessons learned," "Meetings", "Informal dialogue", "Scientific productions" and "EAD".